Radiologic Assessment of Rectosigmoid Cancer Before and After Neoadjuvant Radiation Therapy: Comparison Between Quantitation Techniques - Luccichenti, Giacomo; Cademartiri, Filippo; Sianesi, Mario; Roncoroni, Luigi; Pavone, Paolo; Krestin, Gabriel P (American journal of roentgenology (1976), 2005)
Volumetric analysis was compared with conventional unidimensional measurements for follow-up of rectosigmoid cancer before and after radiation therapy. Fifteen patients with rectosigmoid cancer underwent helical CT before and after neoadjuvant radiation therapy. The helical CT examination was performed after colon distention with air and IV administration of an antiperistaltic drug. Two scans were obtained: one with the patient in the supine position and the other with the patient in the prone position after contrast medium injection. The maximal wall thickness and the volumetric analysis of the tumor were obtained through manual segmentation. The mean of the differences between the volumetric analysis of the scans obtained before and after radiation therapy was 8.3 +/- 10.3 (SD) mL (-22.7%) (p <0.05). The mean of the differences between the maximal wall thickness of the pre- and post-radiation therapy scans was 3.4 +/- 2.6 mm (-19.1%) (p <0.05). A significant difference was observed between the variation of the maximal wall thickness and the variation of volumetric analysis in pre- and post-radiation therapy scans (p <0.05). The patients could be classified in different response categories depending on the measurement method and on the response criteria. Volumetric analysis of rectosigmoid cancer is feasible. A long-term study is needed to correlate volumetric assessment with patient outcome.